A Spin‐Encoded All‐Dielectric Metahologram for Visible Light. Issue 5 (8th April 2019) - Ansari, Muhammad Afnan; Kim, Inki; Lee, Dasol; Waseem, Muhammad Hamza; Zubair, Muhammad; Mahmood, Nasir; Badloe, Trevon; Yerci, Selcuk; Tauqeer, Tauseef; Mehmood, Muhammad Qasim; Rho, Junsuk
Abstract: Dielectric materials that are low‐loss in the visible spectrum provide a promising platform to realize the pragmatic features of metasurfaces. Here, all‐dielectric, highly efficient, spin‐encoded transmission‐type metaholograms (in the visible domain) are demonstrated by utilizing hydrogenated amorphous silicon (a‐Si:H). In comparison to previously reported visible metaholograms based on TiO2 and other dielectric materials, all‐dielectric metasurfaces provide a cost‐effective more straightforwardly fabricated (aspect ratio 4.7), CMOS compatible, and comparably efficient solution in the visible domain. A unique way of utilizing polarization as an extra degree of freedom in the design to implement transmission‐type helicity‐encoded metaholograms is also proposed. The produced images exhibit high fidelity under both right and left circularly polarized illuminations. The proposed cost‐effective and CMOS‐compatible material and methods open up an avenue for on‐chip development of numerous new phenomena with high efficiency in the visible domain. Abstract : A spin‐encoded all‐dielectric metahologram is proposed. A cost‐effective and highly efficient transmission‐type spin‐encoded metahologram is demonstrated by utilizing hydrogenated amorphous silicon (a‐Si:H) nanorods. The size of the metahologram is 400 µm 2 . The single metahologram device is capable of producing off‐axis holographic images at a distance of 200 µm in the propagation direction, depending on the helicity of the incident light.